1979
DOI: 10.1111/j.1476-5381.1979.tb08701.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Uptake Inhibitors on Responses of Sheep Coronary Arteries to Catecholamines and Sympathetic Nerve Stimulation

Abstract: 1 Transmural stimulation of intrinsic sympathetic nerves and exogenous catecholamines produce /I-adrenoceptor mediated relaxant responses in strips of contracted sheep coronary artery.2 The neuronal uptake inhibitors, metaraminol, cocaine and desipramine and the extraneuronal uptake inhibitor, cortisol, failed to potentiate responses to noradrenaline or sympathetic stimulation; responses to isoprenaline were enhanced by cortisol. 3 Oxytetracycline, which inhibits binding to connective tissue fibres, did not af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1982
1982
1993
1993

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…This steroid was shown to inhibit both COMT and uptake in cat heart (Cornish & Goldie, 1980). Alternatively, steroid-induced alteration of Padrenoceptor function has been postulated to explain enhanced catecholamine potency (Besse & Bass, 1966; Yard & Kadowitz, 1972;Brine et al, 1979). It has been shown that increasing the fluidity of cell membranes increases adenyl cyclase activity (Rimon, Hanski, Braun & Levitski, 1978;Bakardjieva, Galla, Helmreich & Levitski, 1979).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This steroid was shown to inhibit both COMT and uptake in cat heart (Cornish & Goldie, 1980). Alternatively, steroid-induced alteration of Padrenoceptor function has been postulated to explain enhanced catecholamine potency (Besse & Bass, 1966; Yard & Kadowitz, 1972;Brine et al, 1979). It has been shown that increasing the fluidity of cell membranes increases adenyl cyclase activity (Rimon, Hanski, Braun & Levitski, 1978;Bakardjieva, Galla, Helmreich & Levitski, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism of steroid-induced potentiation of catecholamine responses has been attributed variously to adrenoceptor sensitization (Besse & Bass, 1966;Yard & Kadowitz, 1972;Brine, Cornish & Miller, 1979), inhibition of catecholamine uptake (Kaumann, 1972;Pun et al, 1973;Goldie, 1976) and inhibition of catechol-0-methyl transferase (COMT) (Kalsner, 1969;Cornish & Goldie, 1980). Indeed, each of these mechanisms may be involved depending upon the tissue, species and steroid used.…”
Section: Introductionmentioning
confidence: 99%
“…and their accompanying pulmonary arteries as well as strips of peripheral parenchyma were dissected from lungs of freshly slaughtered pigs or from macroscopically normal specimens of human lung obtained 4-12 h post mortem. Pulmonary arteries were prepared as described for sheep coronary arteries by Brine, Cornish & Miller (1979 Figure 1). The order of sensitivity to CCh was porcine bronchus > human bronchus > porcine parenchyma > human pulmonary artery > human parenchyma.…”
Section: Methodsmentioning
confidence: 99%
“…B6nisch, Uhlig & Trendelenburg, 1974) and in kitten isolated coronary arteries (Cornish & Goldie, 1980 (Iwasawa, Gillis & Aghajanian, 1973) and rat lung (Nicholas, Strum, Angelo & Junod, 1974) (Junod & Ody, 1977). It is most unlikely that noradrenergic nerves were involved in the accumulation of any of these catecholamines, since sympathetic innervation of airways smooth muscle is sparse or absent below the level of the bronchi in rat (Zussman, 1966;El-Bermani, 1978), guinea-pig (O'Donnell, Saar & Wood, 1978, rabbit and pig lung (Mann, (Hughes, Gillis & Bloom, 1969;Gillis, 1976) where cocaine and imipramine were potent uptake inhibitors (Iwasawa & Gillis, 1974;Nicholas et al, 1974) (Bakhle & Vane, 1974;Gillis & Roth, 1976;Sole et al, 1979) or in vitro (Gillis, 1976 (Bassett, 1971;Picken & Jarrott, 1975;Brine, Cornish & Miller, 1979). Cocaine (10 uM) and desipramine (1 pM), which did not significantly alter the cellular accumulation of radioactivity from [3H]-Iso, also failed to alter significantly the Iso concentrationeffect curves.…”
Section: Radio-tracer Studiesmentioning
confidence: 99%